Intraoperative Flow Measurement by Microflow Probe During Surgery for Brain Arteriovenous Malformations. Issue 2 (23rd March 2015) - Della Puppa, Alessandro; Rustemi, Oriela; Scienza, Renato
Abstract: BACKGROUND: Intraoperative quantitative flow measurement by a microvascular ultrasonic flow probe is an established methodology in aneurysm surgery. OBJECTIVE: To test the present flow measurement procedure in brain arteriovenous malformation (AVM) surgery. METHODS: Data from 25 patients with brain AVMs who consecutively underwent microsurgical resection with the assistance of flow measurement by a microflow probe were retrospectively analyzed. Flowmetry was performed on arterial feeders, potentially transit arteries, and venous drainage of AVM in different phases of resection. RESULTS: A quantitative flow measurement was performed 203 times on 92 vessels. Flowmetry was able to define the flow direction of AVM vessels in all cases, thereby discriminating between arterial feeders and venous drainages, both superficially and deeply located. During AVM dissection, flowmetry identified a transit artery in 12% of cases by detecting a flow drop between 2 points of the same vessel. At the final stage of resection, a residual nidus, potentially missed at surgical dissection, was detected when the flow value of venous drainage was greater than 4 mL/min (20% of patients). Pre-resection microflow probe measurements were concordant with indocyanine green videoangiography data on AVM angioarchitecture in all cases. No microflow probe–induced AVM vessel injury was reported. Complete AVM resection was achieved in all cases with a low morbidity (modified Rankin Scale score ⩽1). CONCLUSION: Multistage intraoperative quantitative flow measurement proved to be a feasible, safe, repeatable, and reliable methodology to assist surgery in different phases of AVM resection. Further studies are needed to assess the impact of this approach on AVM patient outcomes.